Modeling the Offshore Export of Subantarctic Shelf Waters From the Patagonian Shelf - Franco, Barbara Cristie (2018)
It has been suggested that the Subtropical Shelf Front (STSF) could be a preferential site for the detrainment of Subantarctic Shelf Water (SASW) and related planktonic shelf species onto the open SW Atlantic Ocean. The offshore detrainment of SASW and planktonic shelf species might be an exportation mechanism, affecting the population abundances of fishing resources in Argentina, Uruguay, and Southern Brazil. In this study, we characterize for the first time the 3-D structure of the STSF and the main routes of offshore export of SASW from the Patagonian shelf during austral summer (summer and early fall) and winter (winter and early spring) by using numerical hydrodynamical model results and Lagrangian tracking simulations of neutrally buoyant floats. The transport of SASW toward the open ocean is ~1 Sv (1 Sv = 106 m3/s) during summer and ~0.8 Sv during winter. SASW are exported offshore mainly near the Brazil-Malvinas Confluence region during both seasons. The STSF appears to act as an important retention mechanism for the plankton over the inner and middle shelf mainly during late summer and early fall. Our findings could explain the life cycle of distinct fish species that are distributed in the region, as well as the population abundance variability of such species.